Drug discovery from mother nature - Gupta, Subash Chandra; Prasad, Sahdeo; Aggarwal, Bharat B. (Advances in experimental medicine and biology, 2016)
Second comprehensive volume focuses on anti-inflammatory nutraceuticals and their role in prevention and therapy of various chronic diseases. Food and drug administration (FDA) approved drugs such as steroids, non-steroidal anti-inflammatory drugs (NSAIDS), statins and metformin have been shown to modulate inflammatory pathways, but their long-term intake has been associated with numerous side effects. Thus dietary agents which can modulate inflammatory pathways in humans, are likely to exhibit enormous potential. Leading experts describe the latest results of anti-inflammatory nutraceuticals and their role in prevention and therapy of various chronic diseases